UJI EFISIENSI ANODA KORBAN PADUAN ALUMINIUM DAN ZINC MENGGUNAKAN STANDAR UJI DNV RP-B401 TERHADAP VARIASI TEMPERATUR ELEKTROLIT - Rohmannudin, Tubagus Noor; Sulistijono , Sulistijono; Kusuma, Willy Deviet; Sitorus , Grace Aghata (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Corrosion is a decrease in metal quality caused by electrochemical reactions with the surrounding environment. Corrosion is destructive, dangerous, and can cause great losses. Corrosion cannot be stopped but its rate can be controlled. There are many methods that can be used to control the rate of corrosion, one of them is the sacrificial anode cathodic protection. Protection of anode cathodic sacrificial utilizes the principle of a galvanic cell where the metal will be protected or the cathode has a higher potential otherwise the metal will be sacrificed or the anode has a lower potential value. One of the standard practices used to design cathodic protection is DNV RP-B401. By carrying out tests according to the DNV RP-B401 standard, then it can be seen the value of the efficiency of the sacrificial anode working on cathode protection. The efficiency of the sacrificial anode needed to be known to measure the performance of the sacrificial anode in providing protection to the metal to be protected. This research was conducted to determine the effect of differences in electrolyte temperature on the efficiency values of aluminum alloy and Zinc alloy sacrificial anodes. In this study the feasibility test was carried out using electrolyte temperature variations, namely at temperatures of 20°C, 25°C, 30°C, and 35°C. the efficiency results obtained in aluminum alloys for temperatures of 20°C, 25°C, 30°C and 35°C were 88.6%, 80.66%, 76.55% and 63.23%. Then for the Zinc alloys with the same temperature variations were 92.95%, 90.39%, 88.15%, and 77.24%.